2017
DOI: 10.1002/ajmg.a.38551
|View full text |Cite
|
Sign up to set email alerts
|

Intrafamilial variability in the clinical manifestations of mucopolysaccharidosis type II: Data from the Hunter Outcome Survey (HOS)

Abstract: Several cases of phenotypic variability among family members with mucopolysaccharidosis type II (MPS II) have been reported, but the data are limited. Data from patients enrolled in the Hunter Outcome Survey (HOS) were used to investigate intrafamilial variability in male siblings with MPS II. As of July 2015, data were available for 78 patients aged ≥5 years at last visit who had at least one affected sibling (39 sibling pairs). These patients were followed prospectively (i.e., they were alive at enrollment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…The Hunter Outcome Survey (HOS) is a large, global, multicentre, observational registry (Shire, Lexington, MA, USA; NCT 03292887) that was initiated in 2005. The registry collects long-term data on patients with MPS II and the efficacy and safety of ERT with idursulfase [ 5 , 6 , 12 , 16 32 ]. Data from patients in Taiwan have been entered in the registry since 2012.…”
Section: Introductionmentioning
confidence: 99%
“…The Hunter Outcome Survey (HOS) is a large, global, multicentre, observational registry (Shire, Lexington, MA, USA; NCT 03292887) that was initiated in 2005. The registry collects long-term data on patients with MPS II and the efficacy and safety of ERT with idursulfase [ 5 , 6 , 12 , 16 32 ]. Data from patients in Taiwan have been entered in the registry since 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Since Patients A and B carry identical GALNS gene variants, similar phenotypes would be expected (Morrone et al, 2014; Muthukumar Ramalingam et al, 2017). However, it must be noted that intrafamilial variability has been previously described in male siblings with MPS type II and it is possible that it also played a role in the growth outcomes observed in our pair of siblings (Ficicioglu et al, 2018). Specifically, Patient B's skeletal involvement was milder compared to his older brother at the time of treatment, as shown by his skeletal survey obtained shortly after birth (Figure 2b) and also by his physical exam findings throughout the years (Figure 3b‐1,b‐2); in contrast, Patient A presented pectus carinatum, kyphoscoliosis, and reduced extension of the right lower extremities since infancy (Figure 3a‐2,a‐3,a‐4).…”
Section: Discussionmentioning
confidence: 64%
“…This has been suggested for the differences between siblings. After looking at the clinical presentations at different ages, Ficicioglu et al concluded that the chronological age difference between siblings may not have been the cause of discordance [ 13 ]. In our study, the sibling who was least affected was the youngest at 3 years.…”
Section: Discussionmentioning
confidence: 99%
“…He snored while awake and asleep and was not aware of his surroundings. The Japanese study associated frameshift mutation with severe disease [ 13 ].…”
Section: Discussionmentioning
confidence: 99%